From perceptual organization to visual illusions and back - Pinna, Baingio; Porcheddu, Daniele; Skilters, Jurgis (Frontiers in Human Neuroscience, 2022)
In modern vision science, illusions are compelling phenomena useful as tools to explore vision under limiting psychophysical conditions. Illusions manifest at least two issues that challenge scientists. The first issue is related to the definition of illusion and to the complexity of the mismatch between the geometrical/physical and the phenomenal domains. The second issue concerns two different meanings of the term “illusion”, respectively related to the demonstration of the illusion through the mismatch between domains and to the phenomenal illusoriness, i.e., the perception of something having the nature of an illusion, unreal, ambiguous, fallacious and deceptive. In this work we explored the notion of illusion starting from the principles of perceptual organization as described by Gestalt psychologists. On the basis of several phenomenal conditions, step by step, we suggested some new hypotheses, whose purpose was to answer the following questions: What is physical and what is phenomenal? Is there and, if any, what is the dividing line between illusions and non illusions? Is it true that illusions are rare phenomena? Why do illusions exist? What is their perceptual and evolutionist role? These questions and the related issues were phenomenally discussed by deepening and extending the notion of perceptual organization and by exploring the biological implications of both illusions and illusoriness. On the basis of our results, the perception of illusion and illusoriness can be considered as a further challenge for vision scientists useful to shed new insights within the biological meanings of visual perception and within the no-man land between sensory and cognitive processes that elicit visual consciousness not fully explored yet.